Oral desensitization therapy for peanut allergy induces dynamic changes in peanut‐specific immune responses. Issue 8 (14th March 2022) - Bajzik, Veronique; DeBerg, Hannah A.; Garabatos, Nahir; Rust, Blake J.; Obrien, Kimberly K.; Nguyen, Quynh‐Anh; O'Rourke, Colin; Smith, Alex; Walker, Alex H.; Quinn, Charlie; Gersuk, Vivian H.; Farrington, Mary; et al.
Abstract: Background: The PALISADE study, an international, phase 3 trial of peanut oral immunotherapy (POIT) with AR101, resulted in desensitization in children and adolescents who were highly allergic to peanut. An improved understanding of the immune mechanism induced in response to food allergen immunotherapy would enable more informed and effective therapeutic strategies. Our main purpose was to examine the immunological changes in blood samples from a subset of peanut‐allergic individuals undergoing oral desensitization immunotherapy with AR101. Methods: Blood samples obtained as part of enrollment screening and at multiple time points during PALISADE study were used to assess basophil and CD4+ T‐cell reactivity to peanut. Results: The absence of clinical reactivity to the entry double‐blinded placebo‐controlled peanut challenge (DBPCFC) was accompanied by a significantly lower basophil sensitivity and T‐cell reactivity to peanut compared with DBPCFC reactors. At baseline, peanut‐reactive TH2A cells were observed in many but not all peanut‐allergic patients and their level in peripheral blood correlates with T‐cell reactivity to peanut and with serum peanut‐specific IgE and IgG4 levels. POIT reshaped circulating peanut‐reactive T‐cell responses in a subset‐dependent manner. Changes in basophil and T‐cell responses to peanut closely paralleled clinical benefits to AR101 therapy and resemble responses in those with lower clinical sensitivity to peanut. However, no difference in peanut‐reactive Treg cell frequency was observed between groups. Conclusion: Oral desensitization therapy with AR101 leads to decreased basophil sensitivity to peanut and reshapes peanut‐reactive T effector cell responses supporting its potential as an immunomodulatory therapy. Abstract : CRTH2+ pTeff cells and CCR6+ pTeff cells represent two mutually exclusive, nonoverlapping cellular and molecular entities involved in food‐allergic diseases. Circulating CRTH2+ pTeff cells are mostly restricted to peanut‐allergic individuals who react to the 100 mg DBPCFC compared to those with lower clinical sensitivity to peanut. Changes in basophil and T‐cell responses to peanut closely parallel clinical benefits to POIT and resemble responses in those that did not react to the baseline 100 mg DBPCFC.Abbreviations: BAT‐EC50, concentration of allergen corresponding to 50% of maximal activation of basophils in basophil activation test; CCR6, C‐C motif chemokine receptor 6; CRTH2, chemoattractant receptor‐homologous molecule expressed on Th2 cells; DBPCFC, double‐blinded placebo‐controlled peanut challenge; FOXP3, forkhead box P3; freq, frequency; GATA3, GATA binding protein 3; HPGDS, hematopoietic prostaglandin D synthase; IFNG, interferon gamma; IL, interleukin; PALISADE, Peanut Allergy Oral Immunotherapy Study of AR101 for Desensitization in Children and Adults; POIT, peanut oral immunotherapy; PPARG, peroxisome proliferator activated receptor alpha; pTeff, peanut‐reactive T cell; RORC, RAR related orphan receptor C; ST2, suppression of tumorigenicity 2